Management of type 2 diabetes with multiple oral hypoglycaemic agents or insulin in primary care: retrospective cohort study. - Calvert, M; McManus, R; Freemantle, N (2007)
BACKGROUND: Intensive glycaemic control can reduce the risk of microvascular complications in people with type 2 diabetes. AIM: To examine the extent of monitoring and glycaemic control of patients with type 2 diabetes prescribed oral agents and/or insulin, and to investigate transition to insulin. DESIGN OF STUDY: Retrospective cohort study. SETTING: A total of 154 general practices in the UK contributing to the DIN-LINK database between 1995 and 2005. METHOD: People with type 2 diabetes were identified using Read codes and prescribing data. Outcome measures were: glycaemic monitoring and control on multiple oral agents and/or insulin, and transition to insulin. RESULTS: A total of 14 824 people with type 2 diabetes were prescribed multiple oral agents concurrently, of whom 5064 (34.16%) had haemoglobin A(1c) (HbA(1c)) assessments 6 months before and following initiation of their last oral therapy. Mean HbA(1c) before therapy was 9.07%, which dropped to 8.16% following therapy (mean difference 0.91%, 95% confidence interval [CI] = 0.86 to 0.95, P <0.0001). Of the patients with HbA(1c) assessments, 3153 (62.26%) had evidence of poor glycaemic control following therapy. Median time to insulin for patients prescribed multiple oral agents was 7.7 years (95% CI = 7.4 to 8.5 years); 1513 people began insulin during the study and had HbA(1c) assessments 6 months before and following insulin. Mean HbA(1c) before insulin was 9.85% (standard deviation [SD] 1.96%) which decreased by 1.34%, (95% CI = 1.24% to 1.44%) following therapy, but 1110 people (73.36%) still had HbA(1c) > or =7.5%. CONCLUSION: Many people with type 2 diabetes received inadequate monitoring and had poor glycaemic control. Intensive management is required to reduce the risk of microvascular complications.